Pengaruh Likuiditas, Solvabilitas, dan Profitabilitas terhadap Opini Audit Going Concern pada Perusahaan Sub Sektor Farmasi yang terdaftar di Bursa Efek Indonesia - Ainul Ridha; Dedi Prida Sagala (SI-MEN, 2022)
This study to determine the effect of Liquidity, Solvency and Profitability Going Concern Pharmaceutical Sub-Sector Companies listed on the Indonesia Stock Exchange (IDX) for the 2017–2019 period. The sampling technique used the census method with a total of 34 companies. The data testing method used is Multiple Linear Regression Analysis using secondary data. The results of the study show that both simultaneously and partially, Liquidity, Solvency, and Profitability have an effect on Going Concern in Pharmaceutical Sub-Sector Companies listed on the Indonesia Stock Exchange (IDX) for the 2017–2019 period.